2018
DOI: 10.2166/washdev.2018.051
|View full text |Cite
|
Sign up to set email alerts
|

The inactivation of Ascaris suum eggs by short exposure to high temperatures

Abstract: Ascaris sp. is the most prominent and resilient helminth of human health importance found in faecal sludge, making Ascaris sp. an ideal index organism for inactivation testing. Heat treatment destroys helminths, allowing for safe handling and possible reuse of sludge. Technology development focuses on rapid heating to minimize equipment size and cost. This study evaluates Ascaris suum eggs' viability with short heating time. Ascaris eggs were placed in a water bath at temperatures from 60 to 80 °C for various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…We observed complete inactivation of metabolism in larvae treated longer than 3 min. Similar results were reported by Naidoo et al [ 27 , 28 ], who observed inactivation of egg viability and visible egg damage after 3 min of exposure to 60 °C. Further, we evaluated the impact of methanol on A. suum L3 for concentrations up to 25 vol% using the resazurin reduction assay.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed complete inactivation of metabolism in larvae treated longer than 3 min. Similar results were reported by Naidoo et al [ 27 , 28 ], who observed inactivation of egg viability and visible egg damage after 3 min of exposure to 60 °C. Further, we evaluated the impact of methanol on A. suum L3 for concentrations up to 25 vol% using the resazurin reduction assay.…”
Section: Discussionsupporting
confidence: 91%
“…Naidoo et al [ 27 ] have shown that temporary exposure of viable A. suum eggs to 60 °C for various times results in a gradual decrease in egg viability, which was assessed by morphology and motility. Furthermore, methanol-induced feeding inhibition has been reported with gradual effects at concentrations from 1 to 5% [ 18 , 42 ] and a lethal impact for methanol concentrations from 50% in C. elegans [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Temperatures above 70 °C for 120 min effectively inactivated all helminth egg genera ( Maya et al, 2010 ). Furthermore, Naidoo et al (2018) found that Ascaris suum eggs were inactivated when exposed to an 80 °C water bath for four to five seconds, however at 75 °C and 70 °C more time is needed to achieve the same level of inactivation. Harroff et al (2019) indicated that temperatures below 45 ºC could also inactivate A. suum eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Viscous heating at temperatures over 70 °C and 80 °C can achieve complete inactivation of Ascaris spp eggs within 15 and 5 s respectively ( Belcher et al., 2015 , Naidoo et al., 2017 ), additionally, UV irradiation of about 200 to 2000 J/m 2 (using a UV lamp) results in the activation of between 0 and 1.5 log of Ascaris suum eggs ( Brownell and Nelson, 2006 ).…”
Section: Discussionmentioning
confidence: 99%